The Relationship Between Financial Numeracy, Religiosity And Financial Decision Among Islamic Banking Customers In Pakistan - Ansari, Sanaullah (2022)
The concept of financial numeracy has been defined in literature as the combination of financial capacity and financial knowledge. Islamic banking is growing rapidly in the world as it is Riba-free and is the alternate of Riba-based conventional banking system. 96 percent population is Muslim in Pakistan, majority of them did not join conventional banking system due to Riba (Interest). Due to this reason, they could not take their right financial decision to avail any financial product of conventional or Islamic bank. 5 Islamic and 17 conventional banks are offering Islamic banking products and services in Pakistan since 2002, the customers are still unaware about the practicality of these products and services. Therefore, the objectives of this study are to identify and analyze the level of financial capacity, level of financial knowledge and level of religiosity among customers of Islamic banks in Pakistan for joining Islamic banking industry. Further, the impact of financial numeracy and religiosity on financial decision by Islamic banking customers is also analyzed. 500 respondents were selected from Islamic banks in major cities of Pakistan including Islamabad, Rawalpindi, Karachi, Lahore, and Faisalabad to give their answers of a questionnaire. The responses were analyzed with the help of Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structures (AMOS).